Peran Kepala Sekolah Sebagai Supervisor Akademik Dalam Meningkatkan Mutu Pembelajaran (SMP Darul Abrar Al Hasaniyah Balangan -Kalimantan Selatan) - Muhammad Iqbal Ridani; Akhmad Fauzi Hamzah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
We conducted this research with the aim of deeply exploring the principal's role as academic supervisor in improving the quality of learning at SMP Darul Abrar Al Hasaniyah Balangan. Throughout the research process, we sought to understand firsthand how academic supervision practices are implemented, the obstacles encountered, and its impact on student learning processes and outcomes. Using a qualitative case study approach, we went directly to the field, conducted in-depth interviews, actively observed classrooms, and reviewed supporting documents. We selected informants purposively, involving the principal, teachers, educational staff, and students as primary sources of information. Our findings indicate that the principal serves not only as an administrative supervisor but also as a mentor, motivator, and role model for teachers. The academic supervision implemented is participatory and humanistic, with various supporting programs such as classroom observations, teacher discussion forums, in-house training, and ongoing teacher competency development training. We found a positive correlation between active and communicative supervision practices and increased teacher creativity in teaching, a more lively classroom atmosphere, and optimal student learning outcomes. This research further confirms that the principal's role as academic supervisor is a crucial pillar in transforming the quality of learning, particularly through an approach that prioritizes continuous development, character building, and a collaborative learning culture.